Peran Guru dalam Membantu Anak Mengatasi Ketakutan Saat Beradaptasi di TK IT Qur'an Kisaran - Widari, Ayu; Rahman, Mhd Habibu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the role of teachers in helping children overcome fears while adapting to the Kisaran Qur'an IT Kindergarten. Fears often experienced by young children during the transition to school include separation anxiety, fear of new surroundings, fear of unfamiliar teachers and friends, and fear of failure in learning activities. This study is a descriptive qualitative study, with data collection techniques including observation, interviews, and documentation. The results indicate that teachers play a crucial role in assisting children through the adaptation period, employing various strategies, such as individual emotional approaches, active communication with parents, creating a pleasant and Islamic classroom atmosphere, implementing playful methods, and providing positive reinforcement. These strategies help foster a sense of security and comfort for children, enabling them to gradually overcome their fears. Furthermore, teachers' role as role models, demonstrating patience, gentleness, and compassion, significantly contribute to a successful adaptation process. The role of teachers is crucial to the success of early childhood adaptation to the school environment. Teachers who understand children's emotional needs and provide appropriate support can help children navigate the transition with greater confidence and readiness to participate in school activities.